Ibadah dan Perilaku Luhur (Kajian Psikologis dan Sosiologis) - Anisatul Luthfia; Syamsurizal Yazid (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
This research discusses the relationship between worship and noble behavior from both psychological and sociological perspectives, with the aim of identifying how worship, as a form of spriritual devotion, can influence individuals attitudes and behavior in the context of their social life. From a psychological view point, worship is understood as one of the means to achieve psychological well-being, inner peace, and self-control. Regular worship practices, such as prayer, fasting, and dhikr, are expected to enhance positive emotional quality and reduce stress and anxiety. On the other, from a sociological perspective, worship has an important social dimension, as it shapes norms and values in society and strengthens relationships among individuals within the community. Using a theoretical approach and empirical study results, this article concludes that worship performed with full awareness and understanding can be a source of strength for developing noble behavior both psychologically and socially.